Perilaku Hidup Bersih dan Sehat sebagai Upaya Pencegahan Covid-19 pada Masyarakat Usia Produktif - Kharismawati Nur Istiqlal, Dyah Ayu; Wijayanti, Yuni (Indonesian Journal of Public Health and Nutrition, 2023)
Background: Ambarawa Regency is one of the highest contributors to positive Covid-19 cases in Semarang Regency. As many as 2862 COVID-19 cases were recorded in Ambarawa, of which 164 people died. The purpose of this study was to determine the relationship between clean and healthy behavior (CHB) with cases of COVID-19 in people of productive age. Methods: This research is an observational study with a case control approach. The sample in this study amounted to 130 people consisting of 65 people in the case group and 65 people in the control group. The sampling technique used is simple random sampling technique. The instrument used in this study was a questionnaire. The data were processed and analyzed using the chi square test. Results: The results showed that CHB factors associated with Covid-19 were washing hands with soap (p = 0.023), use of hand sanitizers (p = 0.013) and smoking habits (p = 0.031). Meanwhile, the unrelated factor was house disinfection (p = 0.194) and the use of double masks (p = 0.054). Conclusion: The conclusion of this study is that there is a relationship between washing hands with soap, use of hand sanitizers and smoking habits with the incidence of Covid-19.